Exhibition in Ude (The Netherlands) from December 11, 1999 – March 12, 2000: Kopten en Ethiopiërs. Tweeduizend jaar mystiek en christendom langs de Nijl - Marx, Annegret (Aethiopica, 2000)
Conference Review